Effects of Pineapple Juice and Ginger Drink for Relieving Primary Dysmenorrhea Pain among Adolescents - Wrisnijati, Dita; Wiboworini, Budiyanti; Sugiarto, Sugiarto (Indonesian Journal of Medicine, 2019)
Background: Primary dysmenorrhea is characterized by low abdominal pain occurring during menstruation. It is negatively impact on all aspects of life of adolescents such as increased school absteeinsm, emotional disorders, impaired social interaction and productivity. The herbal drink which they can self-prepared is common choice as home remedies to relieve the pain. This study aimed to examine the effect of pineapple juice and ginger drink in providing pain relief to the adolescent with primary dysmenorrhea.Subjects and Method: This was a randomized trial study conducted at three high schools in Surakarta, Central Java, Indonesia, from January to April 2018. A sample of 39 female students aged 15-17 years was selected for this study, divided into three groups. The treatment was given for 3 days from first day of menstruation for 3 menstruation cycles. The pain score were measured by numeric rating scale (NRS). The data were analyzed by Mann-Whitney.Results: Pain score in pineapple juice group (mean= 2.25; SD= 1.79) and ginger drink group (mean= 3.63; SD= 2.02) were lower than control group (mean= 5.64; SD= 1.25) and it was statistically significant.Conclusion: Pineapple juice and ginger drink effective to reduce pain of primary dysmenorrhea among female adolescent.Keywords: Dysmenorrhea, pain, pineapple juice, ginger drink, female adolescentsCorrespondence: Dita Wrisnijati. Masters Program in Nutrition, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. E-mail: ditawrisnijati@gmail.com. Mobile: (62)85742916542.Indonesian Journal of Medicine (2019), 4(2): 96-104https://doi.org/10.26911/theijmed.2019.04.02.03